2021
DOI: 10.1108/tqm-12-2020-0308
|View full text |Cite
|
Sign up to set email alerts
|

Implementing fast track surgery in hip and knee arthroplasty using the lean Six Sigma methodology

Abstract: PurposeOne of the biggest challenges in the health sector is that of costs compared to economic resources and the quality of services. Hospitals register a progressive increase in expenditure due to the aging of the population. In fact, hip and knee arthroplasty surgery are mainly due to primary osteoarthritis that affects the elderly population. This study was carried out with the aim of analysing the introduction of the fast track surgery protocol, through the lean Six Sigma, on patients undergoing knee and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 55 publications
(63 reference statements)
0
13
1
Order By: Relevance
“…Further work used an LSS approach, and in particular the DMAIC (Define, Measure, Analyze, Improve and Control) cycle, to improve the process through a decrease in total length of stay (LOS) (Improta et al. , 2017; Latessa et al. , 2021).…”
Section: Lean Application In Healthcarementioning
confidence: 99%
See 1 more Smart Citation
“…Further work used an LSS approach, and in particular the DMAIC (Define, Measure, Analyze, Improve and Control) cycle, to improve the process through a decrease in total length of stay (LOS) (Improta et al. , 2017; Latessa et al. , 2021).…”
Section: Lean Application In Healthcarementioning
confidence: 99%
“…For example (Improta et al, 2018), demonstrated how Lean thinking led to a reduction in overall time in the emergency department through the implementation of the corrective actions after the Lean interventions. Further work used an LSS approach, and in particular the DMAIC (Define, Measure, Analyze, Improve and Control) cycle, to improve the process through a decrease in total length of stay (LOS) (Improta et al, 2017;Latessa et al, 2021).…”
Section: Lean Application In Healthcarementioning
confidence: 99%
“…Biomedical data analytics is key to improving processes, reducing costs, and giving clinicians new tools to manage all different patients. There are many approaches used in the literature for data analysis, including lean six sigma [ 15 , 16 , 17 , 18 , 19 ], health technology assessment [ 20 , 21 , 22 , 23 ], machine learning algorithms [ 24 , 25 , 26 ], and mathematical modelling [ 27 , 28 , 29 ]. The latter approach was chosen for this study.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that for patients with heart disease the LOS value increases compared to the mean LOS value 12 .The hospital stay and therefore the value of the LOS and the related care costs are lower for patients who are admitted to the Day Hospital 13 . Therefore, in order to reduce hospital costs, it is necessary to plan the surgery as soon as possible which, according to what is reported by the studies in the literature, is also useful for improving the effectiveness of early intervention on the reduction of orthopedic surgery and other surgical processes [14][15][16][17][18][19][20][21][22] In fact, according to the Italian surgical guidelines it is preferable to reduce the risk of complications and the relative stay in the health facility and the relative LOS value [23][24][25][26] .Mathematical modeling was employed in the healthcare sector for several purposes: to optimize medical waste management processes in an Ethiopian hospital 27 ; to forecast the propagation of viruses and bacteria 28,29 ; to predict the LOS of patients undergoing valvuloplasty surgery 30 .…”
mentioning
confidence: 99%
“…The hospital stay and therefore the value of the LOS and the related care costs are lower for patients who are admitted to the Day Hospital 13 . Therefore, in order to reduce hospital costs, it is necessary to plan the surgery as soon as possible which, according to what is reported by the studies in the literature, is also useful for improving the effectiveness of early intervention on the reduction of orthopedic surgery and other surgical processes [14][15][16][17][18][19][20][21][22] In fact, according to the Italian surgical guidelines it is preferable to reduce the risk of complications and the relative stay in the health facility and the relative LOS value [23][24][25][26] .…”
mentioning
confidence: 99%